StreamIt: A Language for Streaming Applications - Thies, Bill; Karczmarek, Michal; Amarsinghe, Saman (International Conference on Compiler Construction (CC 2002). Grenoble, France., 2002)
We characterize high-performance streaming applications as a new and distinct domain of programs that is becoming increasingly important. The StreamIt language provides novel high-level representations to improve programmer productivity and program robustness within the streaming domain. At the same time, the StreamIt compiler aims to improve the performance of streaming applications via stream-specific analyses and optimizations. In this paper, we motivate, describe and justify the language features of StreamIt, which include: a structured model of streams, a messaging system for control, a re-initialization mechanism, and a natural textual syntax